2022
DOI: 10.1186/s13052-022-01271-0
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination coverage in pediatric population in Italy: an analysis of recent trends

Abstract: Background Influenza is a major cause of morbidity, mortality and exacerbation of extant chronic disease worldwide. Influenza vaccination is thus fundamental to reduce the burden of disease. In this study, we describe the trend of influenza vaccination coverage in the seasons 2010/11–2020/21 among children aged < 2, 2–4 and 5–8 in Italy. Methods We analyzed the trend of influenza vaccination coverage in the pediatric population in Italy from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
4
0
1
Order By: Relevance
“…17–20 Vaccination rates in this study population were low, but another recent study found that vaccination rates in Italy more than doubled (reaching 19% for children 2–4 years of age) during the 2020–2021 season, when Italian authorities authorized extended free seasonal influenza vaccination to healthy children 6 months to 6 years old. 11 There are multiple factors that can impact influenza vaccine coverage, including providing free vaccines, perception of vaccine effectiveness or the severity of influenza, and recommendations from healthcare workers. 21 The most recent systematic assessment of influenza vaccine coverage, recommendations and reimbursement in the European Union/European Economic Area (EU/EEA), was conducted in 2018 and found that only 6 of 30 EU/EEA member states recommended vaccination for children and only 3 paid for both the vaccine and its administration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17–20 Vaccination rates in this study population were low, but another recent study found that vaccination rates in Italy more than doubled (reaching 19% for children 2–4 years of age) during the 2020–2021 season, when Italian authorities authorized extended free seasonal influenza vaccination to healthy children 6 months to 6 years old. 11 There are multiple factors that can impact influenza vaccine coverage, including providing free vaccines, perception of vaccine effectiveness or the severity of influenza, and recommendations from healthcare workers. 21 The most recent systematic assessment of influenza vaccine coverage, recommendations and reimbursement in the European Union/European Economic Area (EU/EEA), was conducted in 2018 and found that only 6 of 30 EU/EEA member states recommended vaccination for children and only 3 paid for both the vaccine and its administration.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 However, vaccine coverage for children has been historically low in Europe. 10 , 11 Prior to the coronavirus disease 2019 pandemic, vaccination rates in Italy were <5% for children ≤8 years of age, and although coverage increased significantly after free influenza vaccines for this age group were authorized, >80% of Italian children were not vaccinated against influenza in 2020–2021. 11 …”
mentioning
confidence: 99%
“…Hal ini menyebabkan anak-anak yang berusia lebih rendah dari itu tidak memiliki kekebalan terhadap virus SARS-CoV-2. Oleh karena itu, anak-anak berusia kurang dari 6 tahun sangat perlu diberi vaksinasi Influenza (Ambrosio et al, 2022). Upaya vaksinasi Influenza pada anak dapat menjadi langkah tidak langsung untuk melindungi golongan masyarakat yang rentan semisal para lansia (Tanner, Dorey, & Clark, 2021).…”
Section: Pretestunclassified
“…A high vaccination coverage rate (VCR) is crucial in these populations, as highlighted by international health organizations [ 27 ]. However, several studies conducted worldwide have shown significantly lower levels [ 4 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. To achieve adequate coverage in Italy [ 39 ], the influenza vaccine could be administered at hospitals or tertiary vaccination centers, as well as in general practitioners’ (GP) studies and pharmacies [ 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%